The Effects of 10,000 IU Vitamin D Supplementation on Improvement of Clinical Outcomes, Inflammatory and Coagulation Markers in Moderate COVID-19 Patients: A Randomized-Controlled Trial - Taslim, Nurpudji Astuti; Bukhari, Agussalim; As’ad, Suryani; Rasyid, Haerani; Djaharuddin, Irawaty; Madjid, Mardiana; Olii, Sisca Agustia; Fajri, Zahratul; Syauki, A Yasmin (Nutrición Clínica y Dietética Hospitalaria, 2023)
Background & aims: Vitamin D supplementation as an immunomodulator has been identified as a potential strategy to prevent and treat Coronavirus disease 2019 (COVID-19). We aimed to analyze the effect of 10,000 IU vitamin D3 supplementation on 25(OH)D levels on primary clinical outcomes (conversion length), inflammatory markers (Total Lymphocyte Count (TLC), Neutrophil-to-Lymphocyte Ratio (NLR), Platelet-to-Lymphocyte Ratio (PLR)) and coagulation marker (D-Dimer) in moderate COVID-19 patients at Wahidin Sudirohusodo Hospital, Makassar, Indonesia. Methods: We conducted a single-blind randomized-controlled trial on the confirmed moderate COVID-19 patients above 18 years old and low vitamin D status. Each of intervention and control groups were supplemented of 10,000 IU and 1000 IU cholecalciferol that taken daily for 2 weeks. Levels of 25(OH)D were analyzed for the primary endpoint (conversion length), then correlated to secondary endpoints (Length of Stay (LOS)), clinical manifestations improvement, and markers TLC, NLR, PLR, and D-Dimer serum, handgrip strength (HGS) as functional capacity measurement, after adjusted to age, sex, nutritional status based on body mass index (BMI) and Subjective Global Assessment (SGA) tool, comorbidities, and anti-coagulant administration. Results: The Vitamin D3 supplementation of 10,000 IU and 1000 IU could significantly increase 25(OH)D levels compared to the control group of 1000 IU (4.61+5.43 vs. -0.29+2.72; P <0.0001) and it was correlated to primary clinical outcome, which is length of conversion (6.53+1.17 vs 10.47+2.56; P < 0.0001). The increase in HGS (6.61+3.01 vs. 4.04+4.44; P = 0.011), LOS (11.63+2.5 vs. 14.73+3.45; P = 0.001), and improvement in clinical manifestations were found to be significant in both groups. Conclusion: Supplementation of vitamin D3 10,000 IU in moderate COVID-19 patients had a significant effect on 25(OH)D level, length of conversion, LOS, functional capacity, and PLR levels, but it has negative correlation in TLC, NLR, and D-Dimer levels.